El trabajo docente y la vinculación con la comunidad, de la escuela “provincia del Cañar” de la comunidad de Calerita Santa Rosa, parroquia San Juan, cantón Riobamba, provincia de Chimborazo, año lectivo 2010-2011. - Panata Veloz, Ezabeth Elaudina (2011)
This research project consists in "THE TEACHER WORK AND COMMUNITY ENGAGEMENT, with SCHOOL" PROVINCE OF CANAR "CALERITA of the SANTA ROSA COMMUNITY, SAN JUAN PARISH, and CHIMBORAZO PROVINCE, 2010-2011. To determine the level of engagement that it exists between teachers and community and if there were alternatives to achieve better the integration, through of mechanisms or by means of what activities could achieve a total integration. Data collection was developed through interviews, surveys; direct observation and extensive documentary research it. The teacher work and community engagement was developed in VI chapters which these did not help to understand of better way the teachers work and community engagement, under the Organic Law of Education, it was took place strategies methodological which they led us to attainment of the work. In the proposal were developed seminars-workshops in different areas such as technical production of guinea pigs, ecological gardens, school gardens. Seminar- Workshop on solid fertilizers, liquid fertilizers and genetic improvement of dairy cattle. After evaluating the proposal is concluded that the teaching work and community engagement is very important from the standpoint economic, social, educational, productive, cooperative, and participatory and community work since this leads to a better integration between teacher’s and the community to achieve a solution tone of the many problems as also to improve the living conditions of families that they live in this community.